2020
DOI: 10.1155/2020/4397543
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Chemical Composition, Production, and Pharmaceutical Effects of Kombucha Beverage: A Complementary and Alternative Medicine

Abstract: Kombucha is a valuable traditional natural tea that contains beneficial compounds like organic acids, minerals, different vitamins, proteins, polyphenols, and several anions. Kombucha possesses anticancer, antioxidant, antimicrobial, and antifungal activity as well as hepatoprotective effects. Considering the unique properties of Kombucha, several investigations have already been conducted on its nutritional properties. In this review, an effort has been devoted to pool recent literature on the biomedical appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 62 publications
0
33
0
4
Order By: Relevance
“…eir results demonstrated that M. sylvestris extracts inhibited the in vitro microbial activity. Other studies showed that the seed oil inhibits the growth of all microorganisms tested except the Gram-negative bacteria P. aeruginosa [99][100][101].…”
Section: Antinociceptive Activitymentioning
confidence: 99%
“…eir results demonstrated that M. sylvestris extracts inhibited the in vitro microbial activity. Other studies showed that the seed oil inhibits the growth of all microorganisms tested except the Gram-negative bacteria P. aeruginosa [99][100][101].…”
Section: Antinociceptive Activitymentioning
confidence: 99%
“…Other strategies affecting aging and cell senescence in diseases related to aging including cardiovascular diseases were also mentioned including calorie restriction without malnutrition [ 24 ], Mediterranean diet with olive oil (OO), and the like [ 25 ]. Mostly, the aforementioned dietary components could affect the inflamm-aging process and modulate the oxidative pathways [ 22 , 26 ]. Dietary factors or patterns related to cell senescence are described here in details ( Figure 3 ).…”
Section: Age-related Diseases and Nutritionmentioning
confidence: 99%
“…Several organic acids, including detoxifying glucuronic acid (Martínez- Leal et al, 2020), sugars, polyols, kombucha-specific theobromine, rutin, quercetin and chlorogenic acid, were detected experimentally (Tran et al, 2020;Villarreal-Soto et al, 2020;Barbosa et al, 2021). In vitro assays and model experiments on animals demonstrated antioxidant, anticancer, antiviral, and anti-inflammatory activities (Mousavi et al, 2020). Nonetheless, in vivo assays remain scarce, and clinical trials are lacking to ascertain the health benefits of drinking kombucha (Morales, 2020).…”
Section: Kombucha As Health-promoting Productsmentioning
confidence: 99%